A model for the catalytic activity of microtubule polymerases. Issue 1 (7th November 2022) - Xie, Ping
Abstract: A XMAP215/Stu2/Alp14 polymerase can catalyze processively the tubulin addition to the microtubule (MT) plus end. In this work, a model is proposed for the underlying molecular mechanism of the polymerase activity, where the polymerase can not only catalyze processively the tubulin addition to but also promote the tubulin removal from the MT plus end. Based on the model the dynamics of both the wild‐type and mutant polymerases is studied theoretically, explaining consistently and well various available experimental data. To further test the model, predicted results are provided.